Financial Ratios as Determinants of Firm Value in the Jakarta Islamic Index - Diana Diana Anggraini; Desmon Desmon; Maria Septijantini Alie; Armalia Reny WA; Yudhinanto CN; Susi Indriyani; M. Renandi Ekatama Surya (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study investigates the influence of Current Ratio (CR), Debt-to-Equity Ratio (DER), and Return on Equity (ROE) on firm value, proxied by Price-to-Book Value (PBV), among companies listed in the Jakarta Islamic Index (JII) during 2020–2024. Methodology/Approach: Using a quantitative approach, the study analyzes secondary data from annual financial reports of JII-listed companies on the Indonesia Stock Exchange. From a population of 30 firms (150 firm-year observations), purposive sampling selected 16 companies, yielding 80 firm-year data. Multiple linear regression analysis was conducted using SPSS. Results/Findings: The results show that CR has a significant positive effect on PBV, DER has a significant negative effect, and ROE has a significant positive effect. Simultaneously, CR, DER, and ROE significantly influence PBV, highlighting the combined importance of liquidity, leverage, and profitability in determining firm value. Conclusions: Liquidity and profitability enhance firm value, while higher leverage reduces it. Maintaining optimal financial ratios is essential for improving market valuation and competitiveness in the Islamic capital market. Limitations: The study focuses only on three financial ratios and JII-listed firms during 2020–2024, excluding other potential factors such as macroeconomic conditions. Contributions: This study provides empirical insights for financial management and Islamic capital market research, offering practical value for investors, analysts, and managers in making informed financial and investment decisions.